A feedback control method for the stabilization of a nonlinear diffusion system on the graph - Yu, X.; Xu, C.; Lin, Qun (Institute of Physics Publishing Ltd., 2014)
In this paper, we consider the internal stabilization problems of FitzHugh–Nagumo (FHN) systems on the locally finite connected weighted graphs, which describe the process of signal transmission across axons in neurobiology. We will establish the proper condition on the weighted Dirichlet–Laplace operator on a graph such that the nonlinear FHN system can be stabilized exponentially and globally only using internal actuation over a sub-domain with a linear feedback form.